Cardiac contractility modulation treatment in patients with symptomatic heart failure despite optimal medical therapy and cardiac resynchronization therapy (CRT). (15th February 2019) - Kuschyk, Jürgen; Nägele, Herbert; Heinz-Kuck, Karl; Butter, Christian; Lawo, Thomas; Wietholt, Dietmar; Roeger, Susanne; Gutterman, David; Burkhoff, Daniel; Rousso, Benny; Borggrefe, Martin
Abstract: Background: A significant proportion of patients receiving CRT are non-responders. We evaluated the efficacy of Cardiac Contractility Modulation in subjects with reduced LVEF who, despite cardiac resynchronization therapy (CRT), continued to experience clinically significant symptoms. Methods: This was a multi-center, open label, treatment-only, feasibility study of 17 CRT non-responders who received CCM therapy. Changes in NYHA class, ejection fraction (EF), Minnesota Living with Heart Failure Questionnaire (MLWHFQ) score, and exercise tolerance (6 minute walk test; 6MWT and peak VO2 ) were analyzed over 6 months. Mortality and hospitalization rates were determined. Results: Patients (82% male) were 69.4 ± 9.6 years of age with baseline EF = 22.8 ± 6.5%. Among primary endpoints, peak VO2 increased 1.1 ± 1.6 ml/kg/min ( p = 0.03) and MLWHFQ improved (−16 ± 16 points; p < 0.01). Mean NYHA class improved (−0.33 ± 0.49; p = 0.02), 6MWT increased (52 ± 60 m; p < 0.01), while EF trended up (2.9 ± 5.8%; p = 0.08) at 6 months. During the 6-month follow-up period, there were 18 hospitalizations in 9 subjects and 2 patients died. Conclusions: Patients with heart failure and reduced ejection fraction who remain moderately to severely symptomatic despite use of CRT, may benefit from CCM therapy with improvement in quality of life and exercise tolerance. A larger prospective study in this population is warranted. Highlights: Patients who fail CRT may show symptomatic improvement with addition of CCM therapy. The benefit of CCM + CRT was seen in those with moderate to severe heart failure. The improvement in symptoms and function are not associated with an excess adverse event rate.